2017
DOI: 10.21887/ijvsbt.v13i02.10045
|View full text |Cite
|
Sign up to set email alerts
|

Breeding and Lactation Efficiencies, Production Profile, Productive Herd Life and Lifetime Productivity of Gir Cows in their Home Tract

Abstract: Breeding and lactation efficiencies (BE and LE), parity-wise production profile, productive herd life and lifetime milk production (LTMP) of Gir cows (N=309), based on 1363 calvings during 1991 to 2010 at Cattle Breeding Farm, JAU, Junagadh were studied. Age at first calving (AFC) and calving interval (CI) of Gir cows were 1527.76±14.17 and 481.22±4.86 days, respectively. CI ranged from 386 to 505 days among different lactations. When AFC and CI were taken into account together, BE of the cows as per Tomar (BE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
3
0
1
Order By: Relevance
“…Peak yield and days to attain peak yield observed in this study were in accordance with Patbandha et al (2020) who reported that peak yield was attained in 6-8 weeks after calving. Gaur et al (2003) and Savaliya et al (2016) reported a lower value for dry period but the value of calving interval was similar to the present study whereas Gadariya et al (2017) reported a higher calving interval. The milk composition traits were not affected by the climatic conditions and the results were comparable to other studies.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…Peak yield and days to attain peak yield observed in this study were in accordance with Patbandha et al (2020) who reported that peak yield was attained in 6-8 weeks after calving. Gaur et al (2003) and Savaliya et al (2016) reported a lower value for dry period but the value of calving interval was similar to the present study whereas Gadariya et al (2017) reported a higher calving interval. The milk composition traits were not affected by the climatic conditions and the results were comparable to other studies.…”
supporting
confidence: 88%
“…Results of descriptive analysis and effect of season and stage of lactation on milk production, reproduction and composition traits have been summarized in Table 1. The average TDY was similar to that obtained by Dora et al (2020) for Gir cattle maintained at Chattisgarh but lower than Bangar and Verma (2017) and Gadariya et al (2017) which could be a result of increased humidity as native tract (Gujrat) has hot and arid climate. Gir cattle maintained at Brazil (Araujo et al 2018, Pereira et al 2019) were found to have higher average TDY which could be due to the intense selection practiced in the country for improvement of milk yield.…”
supporting
confidence: 87%
See 2 more Smart Citations